Avaliação das propriedades físico-mecânicas de fibrocimentos produzidos a partir de materiais lignocelulósicos - Teixeira, Julia Naves (2017)
Researches aimed at the development of fiber cement with lignocellulosic residue, in general, use fibers as reinforcement. The use of particles provides lower cost to the production. However, the lack of understanding the behavior of these composites with the addition of particles of many types of reinforcement lignocellulosic materials and the optimum percentage of reinforcement are still a barrier for its use. Thus, this research aimed at evaluating the physical-mechanic properties of the cementitious composites with the addition of different types and percentages of lignocellulosic materials in the form of particles. For conducting this work, particles of eucalypt, banana pseudostem, coffee peel, coconut shells and rice straw were used as reinforcement component for the fiber cement. The lignocellulosic materials were evaluated regarding their physical, chemical and anatomic properties. The composited were produced in laboratorial scale by means of extrusion. The formulation employed in the production of the composites was of: 0, 1, 2, 3, 4 and 5% of lignocellulosic material, 30% of ground agricultural limestone, 1% of hydroxypropyl methylcellulose (HPMC) and 1% of carboxyl polyester additive (ADVA) and, the remaining material, for completing 100% of formulation, was comprised of Portland cement (CPV-ARI). The water/cement relation used was approximately 30% of water. The produced fiber cements were evaluated regarding their physical properties of apparent density, porosity and water absorption; and its mechanical properties of elasticity module, rupture module, proportionality limit and tenacity. The use of lignocellulosic particles as reinforcement of the cement matrix presented satisfactory behavior when evaluating the physical-mechanic properties of the fiber cements produced by extrusion. The best percentages for cement substitution by lignocellulosic particles were of 1% for coffee peel, banana pseudostem and coconut shells, 2% for rice straw and 4% for eucalypt. The fiber cements produced with reinforcement of eucalypt particles presented the best results.